Resorption of implanted bone prepared from normal and warfarin-treated rats. - J B Lian; M Tassinari; J Glowacki (The Journal of Clinical Investigation, 1984)
Bone that was virtually depleted of the vitamin K-dependent protein, osteocalcin, and 93% reduced in the concentration of its characteristic amino acid, gamma-carboxyglutamic acid, was obtained from rats treated with warfarin for 6 wk. Osteocalcin-deficient bone particles were resistant to resorption when implanted subcutaneously in normal rats. The relative resorption was 60% of control bone, as measured by histomorphometry as percent of bone particles in the field. Additionally, the number of multinucleated cells around the bone particles was reduced by 54%. These data suggest that osteocalcin is an essential component for bone matrix to elicit progenitor-cell recruitment and differentiation necessary for bone resorption. Images